Mechanisms Mediating the Effects of γ-Tocotrienol When Used in Combination with PPARγ Agonists or Antagonists on MCF-7 and MDA-MB-231 Breast Cancer Cells - Abhita Malaviya; Paul W. Sylvester (International Journal of Breast Cancer)
γ-Tocotrienol is a natural vitamin E that displays potent anticancer activity, and previous studies suggest that these effects involve alterations in PPARγ activity. Treatment with 0.5–6 μM  γ-tocotrienol, 0.4–50 μM PPARγ agonists (rosiglitazone or troglitazone), or 0.4–25 μM PPARγ antagonists (GW9662 or T0070907) alone resulted in a dose-responsive inhibition of MCF-7 and MDA-MB-231 breast cancer proliferation. However, combined treatment of 1–4 μM  γ-tocotrienol with PPARγ agonists reversed the growth inhibitory effects of γ-tocotrienol, whereas combined treatment of 1–4 μM  γ-tocotrienol with PPARγ antagonists synergistically inhibited MCF-7 and MDA-MB-231 cell growth. Combined treatment of γ-tocotrienol and PPARγ agonists caused an increase in transcription activity of PPARγ along with increased expression of PPARγ and RXR, and decrease in PPARγ coactivators, CBP p/300, CBP C-20, and SRC-1, in both breast cancer cell lines. In contrast, combined treatment of γ-tocotrienol with PPARγ antagonists resulted in a decrease in transcription activity of PPARγ, along with decreased expression of PPARγ and RXR, increase in PPARγ coactivators, and corresponding decrease in PI3K/Akt mitogenic signaling in these cells. These findings suggest that elevations in PPARγ are correlated with increased breast cancer growth and survival, and treatment that decreases PPARγ expression may provide benefit in the treatment of breast cancer.